2014
DOI: 10.1016/j.cub.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Zelda Potentiates Morphogen Activity by Increasing Chromatin Accessibility

Abstract: Summary Zygotic genome activation (ZGA) is a major genome programming event whereby the cells of the embryo begin to adopt specified fates. Experiments in Drosophila and zebrafish revealed that ZGA depends on transcription factors that provide large-scale control of gene expression by direct and specific binding to gene regulatory sequences [1–5]. Zelda (Zld) plays such a role in the Drosophila embryo, where it was shown to control the action of patterning signals [1, 2], however the mechanisms underlying this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
169
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(193 citation statements)
references
References 45 publications
19
169
0
Order By: Relevance
“…Our data and data from others have suggested that ZLD may, in part, mediate transcriptional activation through changes in the chromatin structure (5,24). Therefore, we tested whether the DNA-binding and activation domains that we identified using our transient transfection-based cell culture assay system were necessary and sufficient to activate transcription of a reporter in the context of chromatin.…”
Section: Zld Splice Isoforms Lacking Three Of the Four C-terminal Zinmentioning
confidence: 59%
“…Our data and data from others have suggested that ZLD may, in part, mediate transcriptional activation through changes in the chromatin structure (5,24). Therefore, we tested whether the DNA-binding and activation domains that we identified using our transient transfection-based cell culture assay system were necessary and sufficient to activate transcription of a reporter in the context of chromatin.…”
Section: Zld Splice Isoforms Lacking Three Of the Four C-terminal Zinmentioning
confidence: 59%
“…The recent discovery of the ubiquitous factor Zelda (ZLD) and its role in the regulation of chromatin accessibility (Liang et al 2008;Harrison et al 2011;Foo et al 2014;Xu et al 2014;Schulz et al 2015;Sun et al 2015;Blythe and Wieschaus 2016) and in modulating the timing and strength of BCD-controlled (Xu et al 2014;Hannon et al 2017) and Dorsal-controlled (Foo et al 2014) enhancer activation in a concentration-dependent fashion has further strengthened the hypothesis that the interpretation of the BCD and other morphogen gradients is more complex than previously thought (Lucchetta et al 2005).…”
mentioning
confidence: 92%
“…3A; Supplemental Fig. S9), a ubiquitous activator often described as a pioneer factor active during early embryonic development (Liang et al 2008;Harrison et al 2011;Foo et al 2014;Xu et al 2014).…”
Section: Spatiotemporal Hubs Of Bcd Binding Enrich Local Concentratiomentioning
confidence: 99%
“…Zld protein is present in nuclei considerably earlier than other key maternal transcription factors such as Bicoid (Bcd) and Dorsal (Dl) proteins and is bound to gene regulatory regions prior to zygotic genome activation (Harrison et al 2011;Nien et al 2011). Zld binding increases DNA accessibility and facilitates the binding of other transcription factors, including Bcd and Dl, to target enhancers (Foo et al 2014;Xu et al 2014 (Foo et al 2014). While in vitro nucleosome-binding studies have yet to be reported for Zld, by all in vivo criteria, Zld appears to function as a pioneer factor for zygotic genome activation.…”
Section: Pioneer Factors In Zygotic Genome Activationmentioning
confidence: 99%
“…Inducing zygotic genome activation Liang et al 2008 Increasing DNA accessibility in native chromatin Harrison et al 2011;Foo et al 2014;Xu et al 2014 Class V Pou (e.g., Oct3/4, Pou5f3) Zygotic genome activation (zebrafish/mouse) Inducing zygotic genome activation Foygel et al 2008;Lee et al 2013 Binding to target sites before zygotic genome activation Leichsenring et al 2013 Reprogramming from fibroblast to iPSCs (mouse/human) Inducing reprogramming Takahashi and Yamanaka 2006 Binding to chromatin that is not DNase-sensitive and not premarked by common histone modifications in vivo Soufi et al 2012 Group B1 Sox (e.g., Sox2) Zygotic genome activation (zebrafish/mouse) Inducing zygotic genome activation Pan and Schultz 2011;Lee et al 2013 Reprogramming from fibroblast to iPSCs (mouse/human) Inducing reprogramming Takahashi and Yamanaka 2006 Binding to chromatin that is nonhypersensitive and not premarked by common histone modifications in vivo Soufi et al 2012 Cancer progression (mouse/human) Inducing tumor formation Bass et al 2009;Boumahdi et al 2014 Klf4…”
Section: Updike and Mango 2006mentioning
confidence: 99%